Clinicopathologic and immunohistochemical characterization of 14 cases of angioleiomyomas in oral cavity - Aitken-Saavedra, Juan (Med Oral Patol Oral Cir Bucal, 2018)
BACKGROUND: Angioleiomyoma (ALM) is a benign neoplasm that originates from vascular smooth muscle. It is extremely rare in oral cavity. The objective of this study was to evaluate the clinicopathological and immunohistochemical characteristics of all oral angioleiomyomas registered in a Center of Diagnosis of Oral Diseases from 1959 to 2017. MATERIAL AND METHODS: Slides from 14 cases of ALM stained with hematoxylin and eosin (H&E) were analyzed to confirm the diagnosis. Moreover, an immunohistochemical panel with alpha-smooth muscle actin (alpha-SMA), desmin, AE1/AE3, CD68, S-100, and CD34 antibodies was performed to evaluate semi-quantitatively the positive cells. RESULTS: ALM correspond to 0.08% of all benign oral tumors analyzed during the 57-year period. The mean age of the patients was 45 years with a predilection to males (58%). The most frequently reported site was lips (50%). Microscopic analysis on H&E sections revealed similar pattern in all cases, showing well-circumscribed and encapsulated tumors, characterized by a proliferation of smooth muscle cells and wide vascular spaces of varying sizes. The predominant immuno profiles were: alpha-smooth muscle actin (alpha-SMA) positive (strong immunoreactivity); positive variable pattern for desmin, negative immunoprofile for AE1/AE3, CD68, and S-100. The endothelial cells of vascular spaces were CD34+. CONCLUSIONS: Based on the results, the alpha-SM actin can be elected as a good marker for angioleiomyomas and can help the confirmation of the morphologic diagnosis of this lesion. Key words:Angioleiomyoma, Alpha-SMA, vascular smooth muscle.